2015
DOI: 10.1111/jabr.12043
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder and Public School Teachers: Evaluating Occupational and Health Predictors and Outcomes

Abstract: This study aimed to examine workplace depression among public teachers. Up to 3,003 teachers completed an occupational health survey and Patient Health Questionnaire, which provided provisional diagnoses of major depressive disorder (MDD). Analyses explored key factors linked to MDD among teachers. Teachers more likely to meet MDD criteria were Hispanic, divorced, had less experience, taught at elementary level, reported low job satisfaction and control, and had higher absenteeism and increased likelihood of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…Previous research shows that teachers’ depression scores were significantly higher than the national norm of Chinese adults in several meta-analysis ( Zhang, 2010 ; Zhao, 2015 ), and the incidence of different levels of depressive disorders were high, such as 21.2% of the middle school teachers showing significantly depressive symptoms in Fuzhou ( Luo, 2017 ). Similarly high prevalence of different levels of depression among teachers was also found in other countries such as the United States, the United Kingdom, and Mexico ( Besse et al, 2015 ; Kidger et al, 2016 ; Soria-Saucedo et al, 2018 ). Prior research indicates that depression can negatively affect individual quality of life, job satisfaction, or well-being, and can even increase the risk of suicide ( Ferguson et al, 2012 ; Tsai, 2012 ; Bianchi and Schonfeld, 2016 ).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous research shows that teachers’ depression scores were significantly higher than the national norm of Chinese adults in several meta-analysis ( Zhang, 2010 ; Zhao, 2015 ), and the incidence of different levels of depressive disorders were high, such as 21.2% of the middle school teachers showing significantly depressive symptoms in Fuzhou ( Luo, 2017 ). Similarly high prevalence of different levels of depression among teachers was also found in other countries such as the United States, the United Kingdom, and Mexico ( Besse et al, 2015 ; Kidger et al, 2016 ; Soria-Saucedo et al, 2018 ). Prior research indicates that depression can negatively affect individual quality of life, job satisfaction, or well-being, and can even increase the risk of suicide ( Ferguson et al, 2012 ; Tsai, 2012 ; Bianchi and Schonfeld, 2016 ).…”
Section: Introductionsupporting
confidence: 68%
“…Depression is one of the most common mental health problems among teachers of compulsory education ( Besse et al, 2015 ; Tu, 2017 ; Fu and Zhang, 2019 ). Previous research shows that teachers’ depression scores were significantly higher than the national norm of Chinese adults in several meta-analysis ( Zhang, 2010 ; Zhao, 2015 ), and the incidence of different levels of depressive disorders were high, such as 21.2% of the middle school teachers showing significantly depressive symptoms in Fuzhou ( Luo, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results regarding job satisfaction and control are consistent with the findings of Besse, Howard, Gonzalez, and Howard () who concluded that lower job satisfaction and control significantly predicted major depressive disorder. As depression has been found to be comorbid with somatization, it can be inferred that this relationship holds up between somatization, lower job satisfaction and control (Löwe et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…In Thailand, 2,885,221 people were found to suffer from depression, while 2,275,400 experienced anxiety [1]. Few studies have explored the impact of occupational and personal factors on teachers' mental health and burnout [2][3][4][5]. Some studies have found resilience to be a protective factor for mental health and burnout among teachers [4,6].…”
Section: Introductionmentioning
confidence: 99%